Awareness and Willingness to Pay for Health Insurance: A Study on Selected Government and Non-Government Employees of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: The high cost of health services along with the unpredictability of health needs and the inadequacy of personal savings is the primary reason for the growing importance of insurance as a means of financing health services. Health insurance ensures easy access, high quality, sustainability and affordability of care. This study was undertaken in an attempt to generate some scientific data on awareness and willingness to pay (WTP) for health insurance in our country perspective.Objective: To determine awareness and demand or willingness to pay for health insurance in order to ascertain the feasibility of such schemes and establishing prices.Materials and Methods: This descriptive cross-sectional study was carried out from 1st July 2015 to 30th June 2016 in two governments and two non-government organizations. Randomly 200 government and 200 non-government employees were taken in the sample. A semi structured questionnaire designed to elicit WTP by Contingent Valuation Method (CVM) was used to collect data.Results: Among 400 respondents, 82.8% were male and 17.2% were female. Most of them (85.5%) heard about health insurance earlier and 2.5% subscribed for health insurance. Majority (58.7%) expressed WTP Tk 100-200 (Mean Tk 261.3 ± 196.3) and by percentage of monthly income, average WTP of a formal sector employee was 1.2%. Coverage of health expenditure from employer (10.6%) or insurance (1.1%) side was less and 88.8% of employees had to spend 100% from out of pocket (OOP).Conclusion: Introduction of health insurance, appropriately designed for each population group is imperative for achieving Universal Health Coverage.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 9-13